Dialogic Construction and Interaction in Lodovico Domenichi’s La nobiltà delle donne - Prelipcean, Laura (Renaissance and Reformation / Renaissance et Réforme, 2016)
Lodovico Domenichi (1515–64), one of the major polymaths of sixteenth-century Italy, is currently enjoying a marked revival in the critical literature. Although he has been studied in the context of his contemporary printing and publishing activities, the dissemination of works in the vernacular, the promotion of women’s writings, and the religious crisis of that time, little attention has been devoted to him as a writer. In 1549 Domenichi published a dialogue on and for women, La nobiltà delle donne (The nobility of women). This work allowed him to contribute to the advancement of the women’s cause in Italy. This article investigates how Domenichi modelled the speakers, facilitated their dialogic interaction, and delivered his defence of women. Finally, it sheds light on the role that the female moderator, Violante Bentivoglia, played during the five-day conversations and how she influenced the intellectual and cultural environment dominated by men.